(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2021)
Modern network demands—from ultra-high-definition video to industrial IoT and autonomous vehicles—have pushed traditional architectures to their limits, necessitating next-generation designs focused on highspeed, low-latency, and scalable data communication. Before 2020, key architectural innovations emerged across optical, mobile, and programmable networks. On the optical front, NG-PON2 (Next-Generation Passive Optical Network 2) introduced TWDM-PON with up to 40 Gb/s throughput and compatibility with existing fibre infrastructure . In the wireless domain, MIMO-OFDM became the foundational air interface for 4G and emerging 5G systems, offering exceptional spectral efficiency and throughput by combining multi-antenna transmission with OFDM modulation . At the architectural core of 5G, the Service-Based Architecture (SBA) for the 5G core (5GC)—built on cloud-native, modular network functions—and Network Slicing enabled scalable, tailor-made virtual networks over shared physical infrastructure . Centralized (Cloud) RAN (C-RAN) further optimized radio access by centralizing baseband processing in data centers, enabling resource pooling and reducing latency . Additionally, Software-Defined Networking (SDN) provided programmability and dynamic control, enhancing network adaptability and simplifying traffic handling in next-generation networks . This review integrates these architectural trends to propose a unified framework for high-speed data communication: combining ultra-fast optical access (NG-PON2), efficient wireless transport (MIMO-OFDM), flexible and virtualized core (SBA, network slicing), dynamic RAN (C-RAN), and programmability at scale (SDN). Key insights include enhanced throughput, low latency, multi-service support, and agile resource management. Challenges involve integration complexity, standardization, and deployment cost. Overall, pre-2020 developments laid the foundations for scalable, high-performance network architectures, setting the stage for the mobile and fixed networks powering tomorrow’s digital ecosystem.